Almost Christmas [videorecording (DVD)] - Talbert, David E.; Elise, Kimberly, 1971-; Epps, Omar; Glover, Danny; Mo'Nique; Parker, Nicole Ari; Union, Gabrielle (Universal Pictures Home Entertainment, 2017)
A beloved patriarch asks his family for one gift this holiday season: to get along. If they can honor that wish and spend five days under the same roof without killing one another, it will be a Christmas miracle.